2016
DOI: 10.1175/jas-d-15-0338.1
|View full text |Cite
|
Sign up to set email alerts
|

The Linear Response Function of an Idealized Atmosphere. Part I: Construction Using Green’s Functions and Applications

Abstract: A linear response function (LRF) determines the mean-response of a nonlinear climate system to weak imposed forcings, and an eddy flux matrix (EFM) determines the eddy momentum and heat flux responses to mean-flow changes. Neither LRF nor EFM can be calculated from first principles due to the lack of a complete theory for turbulent eddies. Here the LRF and EFM for an idealized dry atmosphere are computed by applying numerous localized weak forcings, one at a time, to a GCM with Held-Suarez physics and calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 86 publications
3
52
0
Order By: Relevance
“…Furthermore, the strength and latitude of the jet, and w and λ are interconnected (Barnes & Polvani, ; Barnes & Screen, ; Kidston & Vallis, ; Peings et al, , ; Ronalds et al, ). To quantitatively separate the effects of these parameters on each other, controlled experiments using linear response functions can be used (Hassanzadeh & Kuang, , , , ; Khodkar et al, ; Ma et al, ); this is left for future work.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Furthermore, the strength and latitude of the jet, and w and λ are interconnected (Barnes & Polvani, ; Barnes & Screen, ; Kidston & Vallis, ; Peings et al, , ; Ronalds et al, ). To quantitatively separate the effects of these parameters on each other, controlled experiments using linear response functions can be used (Hassanzadeh & Kuang, , , , ; Khodkar et al, ; Ma et al, ); this is left for future work.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Because of the latter, L cannot be derived directly from (3.1)-(3.3). Khodkar et al (2018) showed that L can be accurately calculated using the Green's function (GRF) method (Kuang 2010;Hassanzadeh & Kuang 2016a), which requires many forced DNS of Eqns. (3.1)-(3.3).…”
Section: The 3d Rbc Mathematical Model Dns Solver and 1d Rommentioning
confidence: 99%
“…Linear, time-invariant emulators, of which pattern scaling is a special case, show good fidelity to general circulation model simulations for a wide range of variables and forcings (e.g., Barnes and Barnes, 2015;Kravitz et al, 2016a;MacMartin and Kravitz, 2016;Santer et al, 1990). Other methods, such as Green's function approaches (Hassanzadeh and Kuang, 2016) or application of the fluctuation dissipation theorem (Leith, 1975;Gritsun and Branstator, 2007;Ring and Plumb, 2008;Cooper and Haynes, 2011;Fuchs et al, 2015), are other linear methods that have shown skill in recovering complex climate model behavior. Each of these methods has advantages and disadvantages; there is a great deal of promise in utilizing multiple complementary approaches to understand (linearized) input-output relationships in climate models.…”
Section: Discussionmentioning
confidence: 99%